2022
DOI: 10.1136/bmjoq-2021-001659
|View full text |Cite
|
Sign up to set email alerts
|

Improving hand hygiene in a medical ward: a multifaceted approach

Abstract: BackgroundHand hygiene is a fundamental action which is simple, inexpensive and an effective tool in reducing hospital-acquired infections, yet compliance remains low in healthcare settings. In 2014, Changi General Hospital embarked on a pilot project to improve hand hygiene compliance in a pilot ward with the intention to eventually spread a multifaceted set of interventions hospital wide.MethodsA before and after interventional study of a pilot project. Hand hygiene data collection was through direct observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Research has shown that increasing psychological cues and simplifying operational methods can enhance medical workers' compliance with hand hygiene protocols. [13][14][15][16][17] In line with these findings, it is suggested that hospitals place hand hygiene posters in prominent locations and provide ample, user-friendly hand hygiene facilities for medical personnel. (4) Regular and unannounced hand hygiene inspections are essential to ensure compliance.…”
mentioning
confidence: 82%
“…Research has shown that increasing psychological cues and simplifying operational methods can enhance medical workers' compliance with hand hygiene protocols. [13][14][15][16][17] In line with these findings, it is suggested that hospitals place hand hygiene posters in prominent locations and provide ample, user-friendly hand hygiene facilities for medical personnel. (4) Regular and unannounced hand hygiene inspections are essential to ensure compliance.…”
mentioning
confidence: 82%
“…Interventions to increase healthcare workers' compliance with standard precautions and hand hygiene include but not limited to using a multifaceted set of interventions [9], implementing the WHO's Multimodal Hand Hygiene Improvement Strategy [10], hand hygiene role modelling [11], in-service training about hand hygiene [12], and implementing infection control link nurse (ICLN) programs [13]. The ICLN programs aim to increase health care workers' understanding of infection prevention, create a liaison between hospital wards and the IPC team, and to promote ICLN as a source of information for their peers [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is reported that physicians’ HH performance is lower than nurses’ [ 5 , 12 , 13 ]. Qualitative and small-scale quantitative studies on strategies to overcome these barriers reveal that HH compliance rates can be increased through a multifaceted approach such as educational activities, monitoring and feedback, and placement of HH tools [ 14 , 15 ]. However, there is still a lack of large-scale quantitative studies on barriers to HH compliance and studies considering different occupational groups of HCWs.…”
Section: Introductionmentioning
confidence: 99%